Government and Economic Guidance: Youth Organization Stimulant Assistance - Adi Wijaya (International Journal of Management, Economic, Business and Accounting, 2022)
The purpose of this research was to explain the role of karang taruna in improving social care youth urban village Weru Kidul, District of Weru, Cirebon. This research using of descriptive quantitative, the subject of study was karang taruna member that is in urban village Weru Kidul, District of Weru, Cirebon which consisted of thirty people.. Technique of data collection was using questionsnoire with analisis data using chi square. The result of this research showed that the role of karang taruna in improving social care youth is less good. It means that the youth which attitude responce, care, is to environment around and was consumed by the word his own so tahat they forget with duty of him as youth and members of karang taruna. There fore they are expected to more concerned with their surroundings.